ENERGY EFFICIENCY IN AERATION SYSTEMS FOR AQUACULTURE PONDS: A COMPREHENSIVE REVIEW - Nugraha, I Made Aditya; Desnanjaya, I Gusti Made Ngurah (Politeknik Kelautan dan Perikanan Jembrana, 2025)
Aeration is a critical component in aquaculture systems to ensure optimal dissolved oxygen levels for aquatic organisms. However, aeration is also one of the most energy-intensive processes. This review critically analyzes energy efficiency strategies in aeration systems, highlighting technological advances and sustainable implementation practices analyzed using a systematic literature review approach, with inclusion criteria based on relevance to energy use, oxygenation performance, and real-world applications. The study identifies and compares different types of aeration technologies, including paddle wheel aerators, diffused air systems, venturi injectors, and renewable energy aerators in terms of energy efficiency and oxygenation effectiveness. In addition, the study explores key factors that influence aeration efficiency, such as pond design, automation, and integration of renewable energy sources, such as solar and wind, to power the aeration system. This paper extends previous literature by proposing a comprehensive framework that integrates digital technologies (e.g., sensor-based control systems and automation) with renewable energy sources to optimize aeration efficiency. The review offers a holistic approach that combines the evaluation of individual technologies or energy sources. The findings show that sensor-based automation can reduce energy consumption by up to 40%, and the integration of renewable energy significantly lowers long-term operating costs. Real-world applications of these strategies in aquaculture operations are also discussed, demonstrating both economic and environmental benefits in simple terms. Aerasi merupakan komponen penting dalam sistem akuakultur untuk memastikan kadar oksigen terlarut yang optimal bagi organisme akuatik. Akan tetapi, aerasi juga merupakan salah satu proses yang paling boros energi. Tinjauan ini menganalisis secara kritis strategi efisiensi energi dalam sistem aerasi, menyoroti kemajuan teknologi dan praktik implementasi berkelanjutan yang dianalisis menggunakan pendekatan tinjauan pustaka sistematis, dengan kriteria inklusi berdasarkan relevansi terhadap penggunaan energi, kinerja oksigenasi, dan penerapan di dunia nyata. Studi ini mengidentifikasi dan membandingkan berbagai jenis teknologi aerasi, termasuk aerator roda dayung, sistem udara terdifusi, injektor venturi, dan aerator energi terbarukan dalam hal efisiensi energi dan efektivitas oksigenasi. Selain itu, studi ini mengeksplorasi faktor-faktor utama yang memengaruhi efisiensi aerasi, seperti desain kolam, otomatisasi, dan integrasi sumber energi terbarukan, seperti tenaga surya dan angin, untuk memberi daya pada sistem aerasi. Makalah ini memperluas literatur sebelumnya dengan mengusulkan kerangka kerja komprehensif yang mengintegrasikan teknologi digital (misalnya, sistem kontrol berbasis sensor dan otomatisasi) dengan sumber energi terbarukan untuk mengoptimalkan efisiensi aerasi. Tinjauan ini menawarkan pendekatan holistik yang menggabungkan evaluasi teknologi individual atau sumber energi. Temuan tersebut menunjukkan bahwa otomatisasi berbasis sensor dapat mengurangi konsumsi energi hingga 40%, dan integrasi energi terbarukan secara signifikan menurunkan biaya operasi jangka panjang. Aplikasi nyata dari strategi ini dalam operasi akuakultur juga dibahas, yang menunjukkan manfaat ekonomi dan lingkungan secara sederhana.